Malaria Is Associated with Diminished Levels of Ascorbic Acid: A Systematic Review and Meta-Analysis - Kotepui M. (2023)
Background: It is still unclear how ascorbic acid levels relate to the pathogenesis of malaria. This systematic review synthesized different ascorbic acid levels in malaria patients with different severity levels of malaria and Plasmodium species. Methods: The systematic review protocol was registered in the PROSPERO database (CRD42023394849). A systematic search of PubMed, Embase, MEDLINE, Ovid, Scopus, and Google Scholar was conducted to identify studies that reported ascorbic acid and malaria. The pooled standardized mean difference (Cohen's d) with 95% confidence intervals (CIs) was calculated using the random-effects model. Results: A total of 1480 articles were obtained from the searches of the databases, and 30 studies were included for syntheses. The meta-analysis revealed that patients with malaria had lower levels of ascorbic acid than those without malaria or uninfected controls (p < 0.01, Cohen's d = −3.71, 95% CI = −4.44 to −2.98, I2 = 98.87%, 30 studies). Comparable levels of ascorbic acid were observed between patients with severe malaria and those with nonsevere malaria (p = 0.06, Cohen's d = −1.39, 95% CI = −2.85 to 0.07, I2 = 96.58%, 4 studies). Similarly, levels of ascorbic acid were comparable between patients with Plasmodium falciparum and Plasmodium vivax malaria (p = 0.34, Cohen's d = −1.06, 95% CI = −3.23 to 1.12, I2 = 97.30%, 3 studies). Conclusions: The meta-analysis reveals diminished levels of ascorbic acid in malaria cases. Manipulating the host's nutritional status, such as by supplementing it with ascorbic acid to restore reactive oxygen species balance, may alter the progression of malarial infection and prevention of disease severity.